Comparison of Physiological Outputs of Different Maximum Aerobic Speed Determination Tests - KIZILET, ALİ; BOZDOĞAN, TUBA (MATTIOLI 1885, 2020)
Aim: The aim of the study is to compare blood lactate, VO(2)max and HRmax values after the participants' maximum aerobic speeds (MAS) are determined with 30 seconds running 15 seconds rest interval running test (30-15(IFT)), 45 seconds running 15 seconds resting area incremental interval running test (45-15(FIT)), and incremental treadmill tests. Materials and Methods: The participants of the study are fifteen athletes whose branches are football with an average age of 22.07 +/- 0.69 years. Blood lactate values have been measured with portable lactate measuring device, VO(2)max with gas analyser, and heart rate with GPS running watch during the tests. SPSS 19.0 package program has been used for the statistical analysis of the study. Shapiro Wilk test has been used to assess the suitability of quantitative variables to normal distribution, Friedman test for the comparisons of non-normally distributed variables between 3 dependent groups, Wilcoxon test in 2 dependent group comparisons and Spearman correlation coefficient for the relations between quantitative variables. Results: When the data obtained at the end of 30-15(IFT), 45-15(FIT) (and) treadmill tests were compared, a significant difference was found between the test- end blood lactate (p=0.019), VO(2)max (p=0.006) and maximum aerobic speed (MAS) values (p <0.001). However, when HRmax values obtained from these three tests were compared, no significant difference was found (p=0.683).
Keywords: Blood lactate; oxygen uptake; aerobic speed; interval training; heart rate; HIGH-INTENSITY; TRAINING-PROGRAMS; OXYGEN-UPTAKE; INTERVAL; TIME; PERFORMANCE; VELOCITY